East Asian films in the European market: the roles of cultural distance and cultural specificity. Issue 4 (9th July 2020) - Wang, Xiaoyan; Pan, Haibo Raymond; Zhu, Nibing; Cai, Shaohan
Abstract : Purpose: This study investigates the impact of cultural distance on foreign box office performance of East Asian cinematic production in European markets. Predicated on two dimensions of a film's cultural specificity, namely content- and aesthetics-based components, this research advances current knowledge on the moderating effects of cultural specificity. Design/methodology/approach: The authors compile a data set of 515 East Asian films released in European countries during the 2010–2018 period. Data are analyzed by hierarchical linear modeling. Findings: Results show that cultural distance plays a negative role in affecting foreign box office performance and that aesthetics specificity of films weakens such a relationship, while content specificity of films can further strengthen the relationship. Practical implications: The findings suggest that cultural specificity is a crucial element and a relevant marketing tool in the cross-country film trade. Film producers and distributors need to consider both distribution strategy and intercultural context in order to align effectively with differing cultural distance and specificity. Originality/value: This study proposes a new categorization framework of cultural specificity and demonstrates the moderating roles of content and aesthetics specificity on the relationship between cultural distance and films' foreign box office performance. It offers implications for both theory and practice in global film marketing and trade.